Effects of poloidal magnetic configurations on expansions of electron cyclotron wall conditioning plasma and hydrogen removal in the integrated commissioning phase of JT-60SA - M. Fukumoto; T. Nakano; T. Wakatsuki; S. Kojima; Y. Ohtani; R. Sano; S. Inoue; H. Urano; M. Yoshida (Nuclear Materials and Energy)
Hydrogen (H2) molecules were desorbed from the wall by tokamak discharges with helium (He) working gas. Particle balance analysis revealed that up to the same number of H2 molecules as the injected He atoms were evacuated per He tokamak discharge. Four sequences of Electron Cyclotron Wall Conditioning with He working gas (He-ECWC) performed after the second series of H2 tokamak discharges removed 16% of the H2 molecules that had been retained by the H2 tokamak discharges. The He-ECWC plasma produced by a fundamental ordinary mode (O1-mode) EC wave with a frequency of fEC= 82 GHz expanded along the poloidal magnetic field line. In the He-ECWC plasma produced by the O1-mode EC wave with fEC= 82 GHz, the H2 removal ratio relative to the residual H2 molecules was highest with the poloidal magnetic field in a Trapped Particle Configuration (TPC) with an n-index of 0.7 at the toroidal magnetic field of BT= 1.79 and 2.04 T. A comparable H2 removal ratio was observed with the poloidal magnetic field in a horizontal configuration at BT= 1.79 T. On a second harmonic extraordinary mode (X2-mode) EC wave with fEC= 110 GHz, the He-ECWC plasma was produced locally. For the He-ECWC with the X2-mode EC wave at fEC= 110 GHz, the number of removed H2 molecules did not change significantly between the different poloidal magnetic fields in the TPC at BT= 1.79 and 2.04 T. No He-ECWC plasma was observed with the poloidal magnetic field in the horizontal magnetic configuration at BT= 1.79 and 2.04 T.